PENGARUH JENIS AKTIVATOR DAN UKURAN KARBON AKTIF TERHADAP PEMBUATAN ADSORBENT DARI SERBIK GERGAJI KAYU SENGON (PARASERIANTHES FALCATARIA) - Emi Erawati; Ardiansyah Fernando (JURNAL INTEGRASI PROSES, 2018)
This study aims to determine the effect of activator types and particle sizes on the characteristics of activated carbon from sengon wood sawdust (Paraserianthes falcataria). The characteristics of activated carbon need to be tested to determine the quality of adsorbent, the test includes testing of water content, ash content, the absorption capacity of iodine, and BET (Braunanear, Emmelt, and Teller). Sengon wood powder which has been mashed then sifted using variations of -20, + 40, -40, + 60, -60, + 80, -80, + 100 mesh. temperature of 500°C for 30 minutes. The activated carbon is activated using activators of H3PO4, NaOH, and NaCl with a concentration of 0.1 M in 100 ml. The activation process was soaked for 24 hours, filtered and the residue rinsed with distilled water until the pH was neutral, then oven at 150°C for 3 hours. Active carbon results are tested for quality in accordance with SNI 06-3730-1995. The results of the research in the manufacture of activated carbon from sengon wood powder showed that H3PO4 was the best activator in particle size of -80,+100 mesh, resulting in moisture content, ash content, and iodine absorption of 3.69%, 2.89%, 710.64 mg/g respectively, and . The BET test is carried out at a particle size of -60,+80 mesh of 0.534 m2/ gram.